Oral health needs, habits and parental influences of Trinidadian nursery school children - Maharaj-Gobin, Indira (My University, 1987)
The study aimed to investigate the caries experience, oral health habits and needs of nursery school children. Parental influence on the children’s’ oral health was also investigated. The nursery child is of special interest as there has been an increase in nurseries in recent times. Presently, Dental personnel give extensive Dental Health Education to anti-natal and child welfare groups. The oral health of the pre-school child will assist in Indicating what area oral health education should be aimed at.
A report submitted as part of the requirement of Research Methodology for the dental Nurses Instructor Course of Trinidad and Tobago. Dental Nurses Training School, Arima Hospital Compound.
Keywords: Oral health